Beberapa Problem Teologis Antara Islam dan Kristen - Waryono Waryono (UIN Sunan Kalijaga Yogyakarta, 2011)
Islam, Christian and Jews are closely related religion rooted genealogically from the Father of the Prophet—Abraham. As also human beings, although born from the same ‘worm’, it does not mean appearing similarities. There are always fundamental differences among ‘the children’ made the relationship inharmonic, suspicious, and prejudice. These even become worse if they claim each other and give judgments into another. Islam and Christian both experience the same way. The relationship of the two seems ambivalent and fluctuative, since there are some principal theological differences. This is the urgency of understanding ‘the language of religion’ in an insider perspective to accomplish the more constructive relationship albeit the cause of difference. In this way, the religious followers could meet each other to carry out a noble duty of religion accomplishing a dignified human being through religion.